TEMPOROMANDIBULAR DISC DISPLACEMENT: REVIEW ARTICLE - Bojinovic, Milana; Djurovic Koprivica, Daniela; Maletin, Aleksandra; Puskar, Tatjana; Jeremic Knezevic, Milica (Acta medicae Medianae, 2025)
The articular disc, a resilient structure situated between the surfaces of the temporomandibular joint (TMJ), plays a crucial role in joint function. Composed of dense fibrous tissue and cartilaginous cells, its primary function is to increase the contact surface area under load and ensure even force distribution. Disc dislocation, most commonly anterior or anteromedial, can be either reducible or irreducible. Clinical presentation varies depending on the type of dislocation and the degree of TMJ tissue inflammation. Diagnosis is based on clinical assessment and, when necessary, magnetic resonance imaging (MRI), often prompted by pain. Treatment approaches depend on the type of dislocation; reducible cases may not require intervention, as retrodiscal tissue adaptation can compensate for the disorder. Pain-related dislocations may be managed conservatively with analgesics, muscle relaxants, or reversible occlusal therapy (splints), depending on severity. Acute anterior dislocations without reduction typically require manual reduction followed by stabilization splint use. In chronic cases, a stabilization splint may be used initially to promote retrodiscal tissue adaptation, with surgery considered only if conservative measures fail. Treatment decisions are guided by pain severity, with carefully tailored interventions aimed at alleviating symptoms, restoring joint function, and improving the patient's quality of life.
Keywords: articular disc, temporomandibular joint, disc displacement, splint